Fine-scale diversity in Rhodocybe mellea (Entolomataceae, Basidiomycota), with a description of a new variety and notes on sclerotia formation in Rhodocybe - Xavier, Miguel D.; Silva-Filho, Alexandre G. S.; Wartchow, Felipe; Baseia, Iuri G. (Phytotaxa, 2022)
This study investigates morphological and genetic diversity in Rhodocybe mellea, after a new record of this species in the Brazilian Atlantic Forest. Phylogenetic analysis of molecular data (nrITS and nrLSU) and pairwise genetic distances, provide support for the recognition of cryptic lineages within R. mellea co-occurring in the Neotropics. We propose Rhodocybe mellea var. depressa as morphologically characterized by its depressed pileus, conspicuous sclerobasidia, small flexuous-cylindrical pseudocystidia, and a smooth cutis pileipellis.  In addition, we also determine the position of nrITS sequences of some sclerotium-forming fungi collected in the same area, and confirm the genus Rhodocybe as a producer of this survival structure. Our findings provide unique information on Rhodocybe in South America, and highlight the relevance of approaches that address fine-scale diversity for fungal taxonomy.